BIMBINGAN KELUARGA DALAM MENERAPKAN NILAI-NILAI PENDIDIKAN ISLAM TERHADAP ANAK (Studi Pada Keluarga di Desa Parit Baru RT. 006/RW. 014 Kecamatan Sungai Raya Kabupaten Kubu Raya) - Nurul Wahidah; Sulhatul Hasanah; Hesty Nur Rahmi; Buhori Buhori (PSGA LP2M IAIN Pontianak, 2022)
ABSTRACT Family Guidance is an effort made by parents when educating their children. The purpose of this study was to find out: (1) What Islamic educational values are applied to children through family guidance methods in Parit Baru Village, RT. 006 / RW. 014. (2) How to apply the family guidance method in applying Islamic educational values to children in the family environment in Parit Baru Village RT.006 / RW.014. This research includes field research (Field Research). The method used in this study is a descriptive method with a qualitative approach with data collection techniques of observation, interviews, and documentation. The location of this research is in Parit Baru Village, RT. 006 / RW. 0014 Sungai Raya District, Kubu Raya Regency. Meanwhile, the tools used were observation guide, interview guide, and cellphone. The data validity techniques used in this study were persistent observation, triangulation, and member check techniques. Based on the results of data analysis conducted by researchers, it can be concluded that 1) Parents in Parit Baru Village, RT. 006 / RW. 014 teaches children about Islamic values which include values of faith or aqidah, values of worship, and moral values. 2) Parents in Parit Baru Village, RT. 006/ RW. 014 in guiding children when teaching the values of Islamic education using and applying family guidance methods which include: the example method, the habituation method, the advice method, the reward method and the punishment method.